Parental care in the Shelduck - Hori, John (Wildfowl, 1964)
The behaviour of Shelduck during the brood season is described and discussed. Attacks by adults on their own broods, and the behaviour of ducklings and of birds assumed to be ’failed breeders’ seem to provide a mechanism of crche formation.